Nucleotide diversity of functionally different groups of immune response genes in Old World camels based on newly annotated and reference-guided assemblies - Lado, Sara; Elbers, Jean P; Rogers, Mark F; Melo-Ferreira, José; Yadamsuren, Adiya; Corander, Jukka; Horin, Petr; Burger, Pamela A (BMC genomics, 2020)
BACKGROUND: Immune-response (IR) genes have an important role in the defense against highly variable pathogens, and therefore, diversity in these genomic regions is essential for species' survival and adaptation. Although current genome assemblies from Old World camelids are very useful for investigating genome-wide diversity, demography and population structure, they have inconsistencies and gaps that limit analyses at local genomic scales. Improved and more accurate genome assemblies and annotations are needed to study complex genomic regions like adaptive and innate IR genes. RESULTS: In this work, we improved the genome assemblies of the three Old World camel species - domestic dromedary and Bactrian camel, and the two-humped wild camel - via different computational methods. The newly annotated dromedary genome assembly CamDro3 served as reference to scaffold the NCBI RefSeq genomes of domestic Bactrian and wild camels. These upgraded assemblies were then used to assess nucleotide diversity of IR genes within and between species, and to compare the diversity found in immune genes and the rest of the genes in the genome. We detected differences in the nucleotide diversity among the three Old World camelid species and between IR gene groups, i.e., innate versus adaptive. Among the three species, domestic Bactrian camels showed the highest mean nucleotide diversity. Among the functionally different IR gene groups, the highest mean nucleotide diversity was observed in the major histocompatibility complex. CONCLUSIONS: The new camel genome assemblies were greatly improved in terms of contiguity and increased size with fewer scaffolds, which is of general value for the scientific community. This allowed us to perform in-depth studies on genetic diversity in immunity-related regions of the genome. Our results suggest that differences of diversity across classes of genes appear compatible with a combined role of population history and differential exposures to pathogens, and consequent different selective pressures.
Keywords: Scaffolding; Animals; Immunoproteins; jednonukleotidový polymorfismus; Genome annotation; Camelus; Contig Mapping; Genome assembly; lokus kvantitativního znaku; kontigové mapování; Dromedary; Molecular Sequence Annotation; Genetic diversity; Chromosome conformation capture; zvířata; velbloudi; Quantitative Trait Loci; Chromosome mapping; Polymorphism, Single Nucleotide; anotace sekvence; imunoproteiny; Immune response genes